Regulation of the product stoichiometry of denitrification in intensively managed soils. (5th October 2020) - Wei, Zhijun; Shan, Jun; Chai, Yanchao; Well, Reinhard; Yan, Xiaoyuan; Senbayram, Mehmet
Abstract: Crop residue amendment in conjunction with synthetic nitrogen (N) fertilization is a common agricultural practice that increases soil fertility and crop yield. However, such a practice may also change soil denitrification process. Here, we conducted an incubation experiment with a robotized continuous flow N2 free incubation system [using helium (He) and oxygen (O2 )] and measured fluxes of N2 O and N2 at a high resolution in an intensively managed soil to examine the interaction effect of straw amendment and N fertilization on soil denitrification. Four treatments were set consisting of (a) a nonamended treatment (Control); (b) a Straw treatment (2 g straw kg −1 dry soil); (c) a KNO3 treatment (KNO3, 15 mM KNO3 ); and (d) a Straw + KNO3 treatment (2 g straw kg −1 dry soil and 15 mM KNO3 ). During the oxic phase (80% He plus 20% O2 ) of the experiment (initial 2 days), flux rates of N2 O were 0.54 and 0.38 kg N/ha day −1 in the Control and KNO3 treatments, respectively. Meanwhile, straw amendment triggered N2 O fluxes immediately after the onset of treatments, which was more evident in the Straw + KNO3 treatment. During the anoxic phase (100% He), both N2 O and N2 emissions increased in all treatments, with the effect being more pronounced in the Straw and Straw + KNO3 treatments. In line with the observed differences in gas fluxes, the abundances of nirK, nirS, and nosZ genes increased clearly in these treatments. Overall, the mean N2 O/(N2 O + N2 ) ratio (0.69 ± 0.03) in the Control treatment was significantly lower compared to the KNO3 treatment (18.8%) and higher than the straw‐amended soils (31.9% and 17.4% compared to the Straw and Straw + KNO3 treatments, respectively). Taken together, our results suggest straw amendment significantly altered N2 O and N2 fluxes by decreasing the N2 O/(N2 O + N2 ) ratio; however, the effects of straw amendment depended on soil nitrate content. Abstract : Straw amendment significantly increased denitrification rate; Straw amendment increased denitrification functional gene abundance (especially nosZ); Straw amendment decreased N2 O/(N2 O + N2 ) ratio in an intensively managed soil; the effect of straw amendment on N2 O emission depended on soil NO3 −  level.